Structured Adiwiyata Programs Build Student Ecological Behavior And Sustainable School Cultures: Program Adiwiyata Terstruktur Membangun Perilaku Ekologis Siswa Dan Budaya Sekolah Berkelanjutan - Akbar Wiguna; Rahma Yusrinda; Eka Maghfiroh; Khusnia; Zharfan Muhammad Abdillah (International Consortium of Education and Culture Research Studies, 2024)
General Background Global environmental preservation heavily relies on early ecological education within formal schooling systems. Specific Background SMP Negeri 1 Krembung implements the national Adiwiyata initiative to combat widespread littering habits and foster comprehensive institutional cleanliness. Knowledge Gap Despite widespread implementation, empirical evaluations detailing the specific operational challenges and behavioral transitions within resource-constrained secondary schools remain scarce. Aims This study investigates the operational strategies, institutional barriers, and behavioral outcomes of structured ecological initiatives on the learning community. Results Qualitative analysis involving observations and interviews reveals that routine interventions, including daily plastic collection and weekly communal cleaning, successfully establish sanitation habits. However, significant operational barriers persist, specifically inadequate waste facilities, limited financial resources, and inconsistent teacher enforcement. Overcoming these barriers through fifteen dedicated learner working groups and peer cadres ultimately generated positive disciplinary shifts, resulting in a consistently organized and hygienic environment. Novelty This research explicitly maps the transition from award-oriented policies to practical, learner-led ecological working groups navigating infrastructural limitations. Implications Educational institutions must secure long-term policy support, proactive leadership, and adequate facility funding to transform temporary ecological projects into permanent institutional habits. Highlights: Routine plastic collection and weekly communal cleaning establish consistent sanitation habits. Inadequate waste facilities and limited financial resources severely restrict institutional green initiatives. Dedicated working groups and peer cadres successfully drive positive disciplinary changes. Keywords: Adiwiyata Initiative, Ecological Awareness, Working Groups, Qualitative Evaluation, Institutional Cleanliness